Association of Ki-67 expression in radical cystectomy specimens of infiltrating urothelial carcinoma with histopathological parameters (Bangabandhu Sheikh Mujib Medical University Journal, 2023)
Urothelial carcinoma is the most common neoplasm of urinary bladder. Antigen Ki-67 is a nuclear protein that is necessary for cellular proliferation. The aim of this study was to determine the association of expression of Ki-67 with histopathological parameters in radical cystectomy specimens of histologically diagnosed cases of infiltrating urothelial carcinoma. This is a cross-sectional study conducted among 36 cases of infiltrating urothelial carcinoma collected from Department of Pathology, Bangabandhu Sheikh Mujib Medical University. Histopathological parameters i.e. morphologic variants, stage (pT), lympho-vascular invasion, perineural invasion and lymph node metastasis were assessed. Ki-67 immunohistochemistry were performed. Mean ±SD age of the patients was 58.9±13.8 years. Among the morphological variants, 64% cases were microscopically arranged in papillary pattern. Eighteen (50%) patients underwent surgical intervention at stage pT2. Lympho-vascular invasion, perineural invasion and lymph node metastasis were identified in 12 (33.3%), 9 (25%) and 13 (48.1%) of the cases, respectively. Among the morphological parameters, Ki-67 shows association with pathological stages and lymph node metastasis. The use of Ki-67 immunomarker along with grading and staging may provide significant prognostic information in urothelial carcinoma of the urinary bladder.BSMMU J 2022; 15(3): 186-191